Local community participation towards eco-tourism at Gunung Senyum, Pahang / Nur Ain Mispardi , Nur Raihan Ismail and Alfian Mohd Noor Affindee - Mispardi, Nur Ain; Ismail, Nur Raihan; Noor Affind, Alfian Mohd (Faculty of Hotel and Tourism Management, 2013)
This study discusses the involvement and participation of local communities in tourism development at Gunung Senyum, Pahang. To explore this research topic, the study examines two key concepts which are community participation in the tourism development decision-making process and community participation in the sharing of tourism benefits. Based on the findings obtained, this research concludes that local people wish to play a role in the tourism development decision-making process. In general, local people want to see decisions about tourism development in their area made jointly by government officials and local leaders in consultation with the local community. They also want to be involved in the sharing of tourism benefits. Tourism development is contributing positively to communities and has improved better quality of goods and services, entrepreneurial training, household income and also general quality of life from one aspect to another.